First case report of pustules associated with Escherichia fergusonii in the chinese pangolin (Manis pentadactyla aurita) - Fuyu An; Kai Wang; Shichao Wei; Hongmei Yan; Xuelin Xu; Jinqian Xu; Song Sun; Jiejian Zou; Fanghui Hou; Yan Hua (BMC Veterinary Research, 2023)
Abstract Background Escherichia fergusonii is a common conditionally pathogenic bacterium that infects humans and animals. E. fergusonii has been reported to cause diarrhea, respiratory disease, and septicemia, but it is rarely reported to cause skin infections in animals. E. fergusonii has been isolated from the skin and muscular tissue of Chinese pangolin (Manis pentadactyla aurita). To date, there have been no reports of Chinese pangolins with clinical signs of skin diseases. Case presentation This case report describes the clinical case of a subadult (bodyweight: 1.1 kg) female Chinese pangolin from wild rescue with pustules and subcutaneous suppurative infection due to E. fergusonii in the abdominal skin. Bacterial culture, Biochemical analysis, PCR and histopathology were utilized to identify the bacteria in the pustule puncture fluid and infected tissue. To the best of our knowledge, this is the first report of E. fergusonii-related pustules on a Chinese pangolin. Conclusion This case report presents the first observed skin infection in a Chinese pangolin. E. fergusonii infection should be considered as a possible differential diagnosis of pustules and subcutaneous suppurative skin conditions in Chinese pangolins, and we also provide several recommendations for the diagnosis and treatment of this disease.